The Study of the Effects of Drilled Hole on Tensile Strength of Hybrid Fiber Reinforced Epoxy (HFRE) Composite - Mohd Arshad, Mohamad Hazrul Azli (IRC, 2016)
Hybrid composite materials have great potential for engineering material in many applications. With the recent introduction of hybrid fiber reinforced epoxy (HFRE) composites for industrial applications, the need for evaluating their drill quality is inevitable prior to their final usage of hybrid fiber composite. These materials offer the designer to obtain the required properties in a controlled considerable extent by the choice of fibers and matrix. In the present investigation, the tensile strength of drilled HFRE composite of carbon and glass fiber are studied. The hand lay-up technique was adopted for the fabrication of hybrid composite materials